2009
DOI: 10.1111/j.1365-2249.2009.03880.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of interferon-inducible protein-10 correlates with disease activity and clinical manifestations in systemic lupus erythematosus

Abstract: SummaryOur objective was to investigate the serum levels of interferon-inducible protein-10 (IP-10) in systemic lupus erythematosus (SLE) and their correlation with disease activity and organ manifestations. Serum IP-10 levels were assessed in 464 SLE patients and 50 healthy donors. Disease activity was assessed by the revised SLE Activity Measure, and the concomitant active organ manifestations, anti-ds DNA antibody titres, complement levels and erythrocyte sedimentation rates recorded. Peripheral blood monon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 32 publications
3
60
1
Order By: Relevance
“…They have showed that CCL-2 and CXCL 10 were higher in SLE patients and plasma IL-18 concentration showed strong positive correlation with inflammatory chemokines; CXCL 10 and may be better indicators to assess the current disease activity, prediction of future disease flares and overall clinical decision-making. Our report shows elevated CXCL 10 levels in sera from SLE patients who could serve as good indicators of severity and activity of disease, as suggested by studies conducted at cellular level (Kong et al, 2009). Also, a good association between CXCL 10 and ESR in SLE may suggest Th1 chemokine activity in the disease which may have important roles in leukocyte homing, in the perpetuation of inflammation and concomitant tissue damage (Lee et al, 2009).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…They have showed that CCL-2 and CXCL 10 were higher in SLE patients and plasma IL-18 concentration showed strong positive correlation with inflammatory chemokines; CXCL 10 and may be better indicators to assess the current disease activity, prediction of future disease flares and overall clinical decision-making. Our report shows elevated CXCL 10 levels in sera from SLE patients who could serve as good indicators of severity and activity of disease, as suggested by studies conducted at cellular level (Kong et al, 2009). Also, a good association between CXCL 10 and ESR in SLE may suggest Th1 chemokine activity in the disease which may have important roles in leukocyte homing, in the perpetuation of inflammation and concomitant tissue damage (Lee et al, 2009).…”
Section: Discussionsupporting
confidence: 58%
“…The chemokine CCL 2 (Monocyte chemoattractant protein-1/MCP-1) is known as a Th1 chemokine and has an important role in homing of lymphoid cells to the zone of inflammation (Shimizu et al, 2005). Another chemokine CXCL 10 (Interferon-inducible protein-10/IP-10) upon binding to its ligand CXCR 3 attracts Th1 cells and promotes its maturation (Kong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…18 20 Furthermore, elevated levels of IP-10 were found in patients with pSS related to T-cell infiltration into salivary glands 2122 However, IP-10 has not yet been studied as a biomarker of systemic disease activity in pSS.…”
Section: Introductionmentioning
confidence: 99%
“…31,63 SIGLEC1 and CD64 expression on monocytes also correlated longitudinally with SLE activity. 64 IFN biomarkers have prognostic utility.…”
Section: Type I Interferonmentioning
confidence: 81%